Compliance with Non-Mandatory (Voluntary) Norms of Corporate Governance: Evidence from India - Gupta, Ambrish (Indian Journal of Finance, 2015)
Clause 49 of the listing agreement contains the corporate governance code to be complied with by listed companies in India. The code is divided into mandatory requirements and the non-mandatory (voluntary) ones. Non-compliance of any mandatory requirement with reasons thereof and the extent to which the non-mandatory requirements have been adopted/not adopted needs to be specifically highlighted in the annual corporate governance report. It will be reasonable to assume that companies will necessarily comply with the mandatory requirements in view of the penal provisions for non compliance like fine and delisting among others. However, in respect of voluntary requirements, they have a choice. With this background, the paper sought to examine the extent of compliance/non-compliance of these norms by the listed companies to ascertain whether the corporate sector is complying with the regulatory norms in letters or in spirit. The study found a not too encouraging response.